You are on page 1of 13

# Section 3.

## Indeterminate Forms and LHospitals Rule

THEOREM (LHospitals Rule): Suppose f and g are dierentiable and g (x) = 0 near a (except possibly at a). Suppose that
xa

xa

lim g(x) = 0

or that
xa

xa

## (In other words, we have an indeterminate form of type lim

f (x) f (x) = lim xa g(x) xa g (x) if the limit on the right side exists (or is or ).

## Indeterminate Forms of Type

EXAMPLES: 5x 2 1. Find lim . x 7x + 3 Solution 1: We have 5x 2 [ ] = lim = x x 7x + 3 lim Solution 2: We have
5x2 x 7x+3 x 5x x x 7x x

0 and 0

= lim

2 x 3 x

= lim

5 x 7 +

2 x 3 x

50 5 = 7+0 7

2. Find lim

## x5 + x4 + x3 + x2 + x + 1 . x 2x5 + x4 + x3 + x2 + x + 1 [] x5 + x4 + x3 + x2 + x + 1 lim = = lim x 2x5 + x4 + x3 + x2 + x + 1 x = =

4 3 2 x5 x 1 + x5 + x5 + x5 + x5 + x5 x5 x x x lim 2x5 x4 x3 x2 x 1 x + x5 + x5 + x5 + x5 + x5 x5

Solution 1: We have
x5 +x4 +x3 +x2 +x+1 x5 2x5 +x4 +x3 +x2 +x+1 x5 1 x 1 x

= lim

1+ x 2 +

+ +

1 x2 1 x2

+ +

1 x3 1 x3

+ +

1 x4 1 x4

+ +

1 x5 1 x5

1+0+0+0+0+0 1 = 2+0+0+0+0+0 2

Solution 2: We have [] x 5 + x4 + x3 + x2 + x + 1 (x5 + x4 + x3 + x2 + x + 1) = = lim x 2x5 + x4 + x3 + x2 + x + 1 x (2x5 + x4 + x3 + x2 + x + 1) lim = lim [] 5x4 + 4x3 + 3x2 + 2x + 1 (5x4 + 4x3 + 3x2 + 2x + 1) = = lim x 10x4 + 4x3 + 3x2 + 2x + 1 x (10x4 + 4x3 + 3x2 + 2x + 1) 20x3 + 12x2 + 6x + 2 [ ] (20x3 + 12x2 + 6x + 2) = = lim x 40x3 + 12x2 + 6x + 2 x (40x3 + 12x2 + 6x + 2)

= lim

[] 60x2 + 24x + 6 (60x2 + 24x + 6) = lim = = lim x 120x2 + 24x + 6 x (120x2 + 24x + 6) = lim (120x + 24) 120x + 24 [ ] = lim = x (240x + 24) x 240x + 24 120 120 1 = = x 240 240 2

= lim

3. Find lim

x+2 . x2 ln(x + 3)

Solution: We have

4. Find lim

## 2010 Kiryl Tsishchanka

3x 4. Find lim 2 . x x + x 1 Solution: We have [] 3x (3x ) 3x ln 3 [ ] (3x ln 3) = = lim 2 = lim = = lim x x2 + x 1 x (x + x 1) x 2x + 1 x (2x + 1) lim = lim ln 3 (3x ) ln 3 3x ln 3 (ln 3)2 = lim = lim 3x = (D.N.E.) x x 2 2 2 x

ln x 5. Find lim . x x Solution: We have ln x [ ] (ln x) 1/x 2 lim = = lim = lim 1 1/2 = lim 1/2 = 0 x x ( x) x x x x x 2 6. Find lim 5x tan(5x) . x0 x3 [ ] 0 (5x tan(5x)) 5 sec2 (5x) 5 5x tan(5x) = = lim = lim lim x0 x0 x0 x3 0 (x3 ) 3x2 [ ] 0 5 1 sec2 (5x) 5 (1 sec2 (5x)) = lim = = lim 3 x0 x2 0 3 x0 (x2 ) = 5 2 sec(5x) sec(5x) tan(5x) 5 25 sec2 (5x) tan(5x) lim = lim 3 x0 2x 3 x0 x

Solution: We have

sec2 (5x) tan(5x) 0 Since lim is an indeterminate form of type , we can use LHospitals Rule x0 x 0 again. But it is easier to do trigonometry instead. We have
1 1 sin(5x) sin(5x) sec2 (5x) tan(5x) 25 25 25 cos2 (5x) cos(5x) cos3 (5x) = lim = lim lim 3 x0 x 3 x0 x 3 x0 x ( [ ] ) 1 sin(5x) 25 1 sin(5x) 25 sin(5x) 0 25 = lim lim = lim = = lim 3 x0 cos3 (5x) x 3 x0 cos3 (5x) x0 x 3 x0 x 0

7. Find lim

7. Find lim

## x + sin x . x x + cos x x + sin x [ ] lim = = lim x x + cos x x

x x+sin x x x+cos x x x lim x x x x

Solution 1: We have

## It is easy to show that lim

sin x cos x = 0 and lim = 0 by the Squeeze Theorem. Therefore x x x 1 + sin x x + sin x 1+0 x lim = lim =1 cos x = x 1 + x x + cos x 1+0 x

Solution 2(???): We have x + sin x [ ] 1 + cos x (x + sin x) lim = lim = = lim x x + cos x x 1 sin x x (x + cos x) One can show, however, that lim 1 + cos x does not exist. In fact, we rst note that 1 + cos x x 1 sin x 1 + cos x and 1 sin x may attain any value between 0 and 2. From this one can deduce that 1 sin x 1 + cos x attains any nonnegative value innitely often as x . This means that lim does x 1 sin x not exist, so LHospitals Rule cant be applied here. 8. Find lim
x

sin x . 1 cos x sin x (sin x) cos x = lim = lim = x sin x 1 cos x x (1 cos x)

Solution(???): We have
x

lim

This is WRONG. In fact, although the numerator sin x 0 as x , notice that the denominator (1 cos x) does not approach 0, so LHospitals Rule cant be applied here. The required limit is easy to nd, because the function is continuous at and the denominator is nonzero here: sin x sin 0 lim = = =0 x 1 cos x 1 cos 1 (1) 9. Find lim sin x . x0 x [ ] 0 cos x cos 0 1 sin x (sin x) = = lim = = =1 lim = lim x0 x0 x x0 0 x 1 1 1

Solution(???): We have

The answer is correct, but the solution is WRONG. Indeed, the above proof is based on the sin x formula (sin x) = cos x. But this result was deduced from the fact that lim = 1 (see x0 x Appendix A, page 11). So, the solution is wrong because it is based on Circular Reasoning which is a logical fallacy. However, one can apply LHospitals Rule to modications of this limit (see Appendix B, page 12). 4

## Indeterminate Forms of Type and 0

EXAMPLES: 10. Find lim (x ln x).
x

Solution 1: We have

therefore

## ln x [ ] (ln x) 1/x 1 = = lim = lim = lim = 0 x x x x 1 x x x ( ) ln x lim (x ln x) = lim x 1 = (D.N.E.) x x x lim (

x x x

Solution 2: We have
x

ex x

x1

= (D.N.E.)

1 1 ln x x 1

x1

1 1 ln x x 1

) .

## Solution: We have ( ) [ ] 1 1 x 1 ln x 0 (x 1 ln x) lim = [ ] = lim = = lim x1 x1 ln x (x 1) x1 (ln x (x 1)) ln x x 1 0

1 1 x x 1 (ln x) = lim = lim x1 x1 (ln x) (x 1) + ln x (x 1) x1 + ln x x [ ] x1 0 (x 1) = lim = = lim x1 x 1 + x ln x x1 (x 1 + x ln x) 0

= lim = lim

x 1 1 = lim x1 x 1 + x ln x + x(ln x) x1 1 0 + 1 ln x + x

1 x

1 1 1 = = x1 2 + ln x 2+0 2

## 12. Find lim (sin x ln x). +

x0

Solution: We have [] ln x (ln x) lim (sin x ln x) = [0 ] = lim = = lim + + csc x + (csc x) x0 x0 x0 = lim +
x0

## 1/x sin2 x = lim x0+ x cos x csc x cot x

We can proceed in two dierent ways. Either ( ) sin x sin x sin2 x sin x sin x lim = lim = lim lim = 1 0 = 0 x0+ x cos x x0+ x0+ x x0+ cos x x cos x or [ ] sin2 x 0 (sin2 x) 2 sin x cos x lim = = lim = lim x0+ x cos x x0+ (x cos x) x0+ x cos x + x(cos x) 0 = lim +
x0

2 sin x cos x 2 sin 0 cos 0 201 0 = = = =0 cos x x sin x cos 0 0 sin 0 100 1

## Indeterminate Forms of Type 1 , 0 and 00

EXAMPLES: 13. Find lim
x

)x x+1 Solution 1: Note that lim is 1 type of an indeterminate form. We have x x+2 ( )x ( )x x+1 x+21 lim = lim x x x+2 x+2 ( )x x+2 1 = lim x x+2 x+2 ( )x 1 = lim 1 x x+2 ( = lim
x

x+1 x+2

)x . (

1 1+ x 2

x )(x2) x2

[( = lim [ =
u x

1 1+ x 2 1 1+ u )u

x )x2 ] x2

( lim

] =e

= lim e x2
x lim

## = ex x2 = ex (x2) = e1 COMPARE: We have

x lim
x

( lim

x+1 3x + 2 and )x

)x =0 ( )x 1 lim =0 x 3

since

1 x+1 = lim x 3x + 2 3 (
x

Similarly, lim

3x + 1 x+2

## = (D.N.E.) lim 3x = (D.N.E.)

since

3x + 1 = 3 and x x + 2 lim 7

Solution 2: We have ( )x ln( x+1 ) [ 0 ] ln( x+1 ) x+2 x+2 x+1 x x+1 lim ln(( x+2 ) ) x ln( x+1 ) 1 x+2 lim = lim e = lim e = lim e x = ex x1 = e( 0 ) x x x x x+2
lim
x+1 (ln( x+2 )) (x1 ) x+2 (x+1) (x+2)(x+1)(x+2) x+1 (x+2)2 x2 x

= ex

=e

lim

=e

lim

=e

## x+2 1 x+1 (x+2)2 2 x x

lim

=e

1 (x+1)(x+2) x2 x

lim

=e

lim

x2 x (x+1)(x+2)

x+1 x+2

)x ( )

## x+1 (( )x ) ( ) ln x+1 x+1 x+2 ln y = ln = x ln = x+2 x+2 x1 ( )

We have x+1 ln x+2 lim x x1 ( ( )) ( ) x+1 x+1 x+2 [ ] ln 0 x+2 x+1 x+2 = = lim = lim 1 ) 2 x x 0 (x x

x + 2 (x + 1) (x + 2) (x + 1)(x + 2) x + 2 (x + 2) (x + 1) 2 x+1 (x + 2) x+1 (x + 2)2 = lim = lim x x x2 x2 x+2 1 1 [] 2 x2 x + 1 (x + 2) (x + 1)(x + 2) = lim = lim = lim = x x x (x + 1)(x + 2) x2 x2 = lim (
x

1+

1 x

1 )(

1+

2 x

) =

1 = 1 (1 + 0) (1 + 0) ( x+1 x+2 )x = e1

Therefore
x

lim

x

1 1+ x

)x .

x

1 1+ x

)x . (
x

## Solution: We have lim

1 1+ x

)x =e

by denition of e. Note, that we cant use the approach described in Example 13, since it is based ( )x 1 1 of the formula (ln x) = . But this result was deduced from the fact that lim 1 + =e x x x (see Appendix A, page 11). This is Circular Reasoning which is a logical fallacy. However, one can apply LHospitals Rule to modications of this limit. 15. Find lim (1 + sin 7x)cot 5x . +
x0

Solution 1: Note that lim (1 + sin 7x)cot 5x is 1 type of an indeterminate form. Put +
x0

y = (1 + sin 7x)cot 5x then ( ) ln y = ln (1 + sin 7x)cot 5x We have = ln y = cot 5x ln(1 + sin 7x) = cos 5x ln(1 + sin 7x) sin 5x

[ ] 0 cos 5x ln(1 + sin 7x) ln(1 + sin 7x) lim = = lim cos 5x lim x0+ x0+ x0+ sin 5x 0 sin 5x
1 1+sin 7x

[ ] ln(1 + sin 7x) 0 [ln(1 + sin 7x)] = lim = = lim = lim x0+ x0+ x0+ sin 5x 0 (sin 5x) = lim +
x0 1 1+sin 7x

## cos 7x 7 7 = cos 5x 5 5 lim (1 + sin 7x)cot 5x = e7/5

Therefore
x0+ x0

Solution 2: Note that lim (1 + sin 7x)cot 5x is 1 type of an indeterminate form. We have + lim (1 + sin 7x)cot 5x = lim eln((1+sin 7x) + +
x0
x0+ cot 5x

x0

x0 x0

=e

lim

## cos 5x ln(1+sin 7x) sin 5x

[ ] [ ] ln(1+sin 7x) ln(1+sin 7x) lim cos 5x lim lim 0 0 sin 5x sin 5x x0+ x0+ x0+ = =e =e = 0 0
1 1+sin 7x (1+sin 7x) cos 5x5 x0+

=e

lim

=e

lim

=e

lim

= e7/5

x/2

## 16. Find lim (tan x)2x .

x/2

Solution: Note that lim (tan x)2x is 0 type of an indeterminate form. Put
x/2

## y = (tan x)2x then ( ) ln y = ln (tan x)2x ln(tan x) (2x )1

ln y = (2x ) ln(tan x) =

We have
1 [] sec2 x ln(tan x) [ln(tan x)] tan x = = lim = lim x/2 (2x )1 x/2 (1)(2x )2 2 x/2 [(2x )1 ]

lim

[ ] 1 1 1 (2x )2 0 1 [(2x )2 ] sin x cos x = lim = lim = = lim 2 x/2 (2x )2 2 x/2 cos x 0 2 x/2 (cos x) = Therefore lim (tan x)2x = e0 = 1
x/2

x0

## Solution: Note that lim xx is 00 type of an indeterminate form. Put +

x0

y = xx then ln y = ln xx We have ln x [ ] (ln x) 1/x lim (x ln x) = [0 ] = lim 1 = = lim = lim + + x + (x1 ) + x2 x0 x0 x0 x0 = lim +
x0

ln y = x ln x

Therefore
x0+

x0

10

## 18. Find lim (tan 5x)x . +

x0

Solution: Note that lim (tan 5x)x is 00 type of an indeterminate form. Put +
x0

## y = (tan 5x)x then ln y = ln(tan 5x)x We have

x0

ln y = x ln(tan 5x)

x0 1 tan 5x

## ln(tan 5x) [ ] (ln(tan 5x)) = = lim + x0 1/x (1/x)

sec2 5x 5 x2 sec2 5x x2 = lim = 5 lim = 5 lim x0+ x0+ tan 5x x0+ sin 5x cos 5x 1/x2 [ ] x2 1 x2 0 = 5 lim lim = 5 lim = + sin 5x + cos 5x + sin 5x x0 x0 x0 0 = 5 lim +
x0 x0

## Therefore lim (tan 5x)x = e0 = 1 + 19. Find lim (sin 2x)tan 3x . +

x0

Solution: Note that lim (sin 2x)tan 3x is 00 type of an indeterminate form. Put +
x0

## y = (sin 2x)tan 3x then We have

x0

( ) ln y = ln (sin 2x)tan 3x

x0

x0 x0

## 1 = lim (sin 3x ln(sin 2x)) = [0 ] cos 3x x0+

= lim +
x0

1 cos 2x 2 ln(sin 2x) [ ] [ln(sin 2x)] = = lim = lim sin 2x + + csc 3x cot 3x 3 x0 x0 csc 3x (csc 3x) 1 cos 2x sin 2x 1 cos 3x sin 3x sin 3x

## [ ] 2 0 2 sin2 3x cos 2x sin2 3x lim = lim = = lim + sin 2x + cos 3x + sin 2x x0 3 x0 3 x0 0

2 2 (sin2 3x) 2 sin 3x cos 3x 3 lim = lim =0 3 x0+ (sin 2x) 3 x0+ cos 2x 2
x0+

11

## 2010 Kiryl Tsishchanka

Appendix A
THEOREM: The function f (x) = sin x is dierentiable and f (x) = cos x Proof: We have (sin x) = lim sin(x + h) sin x h0 h

[We use sin( + ) = sin cos + cos sin ] ( ) sin x cos h + cos x sin h sin x sin x cos h sin x cos x sin h = lim + = lim h0 h0 h h h ( ) sin x(cos h 1) sin h cos h 1 sin h = lim + cos x = sin x lim + cos x lim h0 h0 h0 h h h h = sin x 0 + cos x 1 = cos x THEOREM: The function f (x) = loga x is dierentiable and f (x) = Proof: We have 1 x ln a

[ ( )] loga (x + h) loga x 1 x+h d (loga x) = lim = lim loga h0 h0 h dx h x ( )] [ ( )] 1 1 x h h = lim loga 1 + = lim loga 1 + h0 h h0 x h x x [ [ ( ( )x/h ] )1/(h/x) ] h h 1 1 = lim loga 1 + = lim loga 1 + x h0 x x h0 x [ ( )1/(h/x) ] [ ] 1 1 h 1 ln e 1 = loga lim 1 + = lim (1 + u)1/u = e = loga e = = u0 h0 x x x x ln a x ln a [

12

## 2010 Kiryl Tsishchanka

Appendix B
1. Find lim sin x . 2x [ ] sin x 0 (sin x) cos 0 1 cos x lim = = lim = lim = = x0 2x x0 (2x) x0 0 2 2 2 [ ] sin x 0 1 sin x 1 1 lim = = lim = 1= x0 2x 0 2 x0 x 2 2

x0

Solution 1: We have

Solution 2: We have

2. Find lim

sin 2x . x0 x [ ] 0 2 cos 0 sin 2x (sin 2x) 2 cos 2x lim = = lim = lim = =2 x0 x0 x0 x 0 x 1 1 [ ] sin 2x 0 sin 2x lim = = 2 lim =21=2 x0 x0 2x x 0

Solution 1: We have

Solution 2: We have

3. Find lim

sin 2x . x0 5x [ ] sin 2x 0 (sin 2x) 2 cos 2x 2 cos 0 2 lim = = lim = lim = = x0 5x x0 (5x) x0 0 5 5 5 [ ] sin 2x 0 2 sin 2x 2 2 lim = = lim = 1= x0 5x 0 5 x0 2x 5 5

Solution 1: We have

Solution 2: We have

4. Find lim

sin 2x . x0 sin 5x [ ] sin 2x 0 2 cos 2x 2 cos 0 2 (sin 2x) lim = = lim = = = lim x0 sin 5x x0 5 cos 5x x0 (sin 5x) 0 5 cos 0 5

Solution 1: We have

## Solution 2: We have [ ] 0 sin 2x = lim = lim x0 sin 5x x0 0

sin 2x 2x sin 5x 5x

2x 1 2x 2 2 = lim = lim = x0 1 5x x0 5 5 5x

13